Başlangıçtan günümüze İstanbul’daki fotoğrafhaneler - Bölük, Gülderen (My University, 2010)
The earliest reference to foreign photography studios in Istanbul dates back to 1839, to the announcement of the Daguerre’s invention of photography in Ottoman Press. After 1850s Ottoman Citizens, mainly coming from Armenian and Greek origins, start opening their own studios one after the other. It took another 60 years for Muslim studios to take their place in the history of Ottoman photography. The studios were primarily concentrated in Beyoğlu and Historical Peninsula districts. The very first studios in Kadıköy and Üsküdar districts came on the scene only at the end of the century. The studios, generally located in multi-storey buildings at central districts, were highly qualified with technical hardware and furnishings imported from Europe. Besides portrait photography they had also derived revenues from landscape photography, postcards and photographic series based on themes like professions, Dynasty and diplomatic missionary. Not only the technical fixture but also the technical implementation in the studios also differs from year to year. All items and details ranged from the variety of backgrounds, settings and accessories to darkroom equipment reflect this change. The social history of the era can also be traced back in the photographs taken in these studios. The contemporary fashions, socio- cultural atmosphere, popular cinema and film artists of the day continuously inspired the pose and the mimics of the studio clients. Furthermore the studios have also been under the influence of different art movements. After its first appearance in 1839, the photography is asserted to be the successor of painting, due to its high documentation qualities. Nevertheless photography has also influenced painting in the following eras. Orientalism continued to affect photography even after it came to an end in painting. Although there has never been an art movement originated primarily in relation to studios, it can be said that movements in art, mainly Romanticism and Neo-classism also affected studio photography. Contrary to its progress in the Western world, Turkish photography rooted from the studios even though it has been characterized further by the integration of press photography, the politics of the Republic, the photographic tradition in the community centres and other social, cultural, political and technical influences of its age. Nevertheless, this means that it is not possible to comprehend Turkish photography fully without analyzing the studio period dating back to the very first institutions in this field.
Keywords: Fotoğraf; İstanbul (Türkiye)_Fotoğrafçılık